In Vivo and In Vitro Acquisition of Resistance to Voriconazole by Candida krusei - Ricardo, Elisabete (American Society for Microbiology, 2014)
Candida krusei is an important agent of opportunistic infections that often displays resistance to several antifungals. We describe here the in vivo acquisition of resistance to voriconazole (VRC) by C. krusei isolates recovered from a leukemia patient during a long period of VRC therapy. In order to mimic the in vivo development of VRC resistance, a susceptible C. krusei isolate was exposed daily to 1 μg/ml of VRC in vitro. Interestingly, after 5 days of exposure to VRC, a MIC of 4 μg/ml was achieved; this value remained constant after 25 additional days of treatment with VRC and also after 30 consecutive days of incubation in VRC-free medium. Our objective was to determine the associated molecular resistance mechanisms, such as expression of efflux pump genes and ERG11 gene mutations, among the resistant strains. Synergistic effects between the efflux blocker tacrolimus (FK506) and VRC were found in all of the resistant strains. Moreover, ABC1 gene expression increased over time in both the in vivo- and in vitro-induced resistant strains, in contrast to the ABC2 and ERG11 genes, whose expression was invariably lower and constant. ERG11 gene sequencing showed two different types of mutations, i.e., heterozygosity at T1389T/C, corresponding to synonymous mutations, in C. krusei strains and a missense mutation at position T418C, resulting in a change from Tyr to His, among resistant C. krusei clinical isolates. This study highlights the relevance of ATP-dependent efflux pump (namely, Abc1p) activity in VRC resistance and describes new mutations in the ERG11 gene among resistant C. krusei clinical isolates.